Morphology and bioactive compounds of gurmar (Gymnema sylvestre) with potential as antidiabetics - Yuliany, Neny Novita; Farhan, Abdillah Maulana; Ziyaroh, Putry Lazimatu; Dwinianti, Edia Fitri; Nihayah, Husnatun; Su'udi, Mukhamad (Universitas Padjadjaran, 2026)
The medicinal plant Gymnema sylvestre is widely known for its ability to lower blood sugar levels. This study reviewed the physical characteristics and bioactive compounds of G. sylvestre sourced from different regions, emphasizing its potential as an antidiabetic agent. Morphological analysis includes leaf structure, trichome presence, and other anatomical features, which can influence the plant's chemical profile. Phytochemical analysis, performed using techniques like GC-MS, identifies key bioactive compounds such as saponins, flavonoids, and gymnemic acids, which contribute to its hypoglycemic effect. The findings indicate that regional variations can affect the concentration and presence of these compounds, suggesting that environmental factors and genetic diversity play significant roles. This comprehensive characterization supports the use of G. sylvestre as a natural antidiabetic treatment, which supports its potential as a source of antidiabetic-related bioactive compounds. Further research is recommended to explore the pharmacological mechanisms and optimize the extraction methods for maximum efficacy.